A new species of Pelagodes Holloway, 1996 and a new species of Thalassodes Guenée, 1857 from Luzon, the Philippine islands (Lepidoptera: Geometridae, Geometrinae, Thalassodini) - A. Lindt; K. Sarv; J. Viidalepp (SHILAP)
Two new species of Thalassodini, Pelagodes tuustiae Lindt, Sarv & Viidalepp, sp. n. and Thalassodes lennuki Lindt, Sarv & Viidalepp, sp. n., are described from Luzon, Philippines. The adults, their male and female genitalia characteristics are described and illustrated.